Prenatal diagnosis of tuberous sclerosis in association with rhabdomyomas: case report and discussion of the importance of molecular diagnosis - Vallenas Campos, Rosa E. (2024)
Tuberous sclerosis complex (TSC) is characterized by the development ofhamartomas in various tissues. We present the case of a 39-year-old female patientwith a 24-week-old fetus with multiple rhabdomyomas in whom a prenatal moleculardiagnosis of TSC was made. With the diagnosis confirmed, postnatal evaluation wasextended, finding hypopigmented macules in the skin and multiple cortical andsubependymal tubercles. In the family evaluation, the father presented cutaneouslesions and is under study to confirm TSC. At 6 months of age, the infant remainsasymptomatic. The diagnosis of prenatal TSC has an impact on the prognosis ofthe patient and family. It improves the postnatal neurological prognosis, allowsextending the search for the disease to parents and siblings, and provides tools formore accurate pregnancy counseling and family planning.